2014
DOI: 10.1155/2014/964614
|View full text |Cite
|
Sign up to set email alerts
|

Female Aging Alters Expression of Human Cumulus Cells Genes that Are Essential for Oocyte Quality

Abstract: Impact of female aging is an important issue in human reproduction. There was a need for an extensive analysis of age impact on transcriptome profile of cumulus cells (CCs) to link oocyte quality and developmental potential with patient's age. CCs from patients of three age groups were analyzed individually using microarrays. RT-qPCR validation was performed on independent CC cohorts. We focused here on pathways affected by aging in CCs that may explain the decline of oocyte quality with age. In CCs collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 65 publications
(71 reference statements)
1
60
0
Order By: Relevance
“…Oocyte aging has been proposed to occur in association with mitochondrial dysfunction resulting from the accumulation of point mutations and decreased mtDNA content [5,19]. Several studies demonstrated an aberrant gene expression profile in aged CCs [20,21]. However, little information is available concerning mitochondrial dysfunction in aged CCs.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte aging has been proposed to occur in association with mitochondrial dysfunction resulting from the accumulation of point mutations and decreased mtDNA content [5,19]. Several studies demonstrated an aberrant gene expression profile in aged CCs [20,21]. However, little information is available concerning mitochondrial dysfunction in aged CCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of this study, we observed down-regulated expression of this gene in porcine COCs after IVM comparing to before IVM. It suggests that TGFBR3 is involved in maturation-related mechanism, however we cannot exclude its role in processes related to cumulus cells differentiation as well [1], since TGF/TGFB/TGFBR signaling cascade between oocytes and follicular cells maintains considerably higher activity at early stages of oogenesis and folliculogenesis. Thus, TGFB-TGFBR3 signaling in porcine oocytes and follicular cells may be essential for proper growth, development, and maturation.…”
Section: Discussionmentioning
confidence: 88%
“…Fragouli et al (2010) also observed several genes involved in pathways related to hypoxia to be upregulated in their analysis of human aneuploid oocytes. Al-Edani et al (2014) observed an increased expression of angiogenic genes in aged cumulus cells and hypothesised that these genes were being upregulated in an attempt to neutralise the deleterious effects of a hypoxic environment. Our findings, in combination with those of Fragouli et al (2010) and Al-Edani et al (2014), indicate that there could be insufficient oxygen in these cells and, thus, increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Edani et al (2014) observed an increased expression of angiogenic genes in aged cumulus cells and hypothesised that these genes were being upregulated in an attempt to neutralise the deleterious effects of a hypoxic environment. Our findings, in combination with those of Fragouli et al (2010) and Al-Edani et al (2014), indicate that there could be insufficient oxygen in these cells and, thus, increased oxidative stress. Although it seems counterintuitive to have a hypoxic environment with high levels of oxidative stress, it has been shown that superoxide generation can be elevated in response to both high and low levels of oxygen (Clanton 2007).…”
Section: Discussionmentioning
confidence: 99%